INVARIANT SYSTEM OF AUTOMATIC WATER-LEVEL REGULATING IN THE BOILER SHELL - G. T. Kulakov; A. N. Kuchorenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The quality of water-level regulation in the boiler-shells of heat-power and nuclear-power plants largely determines reliable and economical operation. The latter can be accomplished by means of massive reduction of the actuation-mechanism running time which depends directly on the regulator performance.The paper examines some foreign methods of PID-regulator adjusting in the cascade system of boiler-shell water-level automatic regulation. The authors derive an invariant cascade system of automatic regulation in which they offer not to measure external disturbance, the steam rate for instance, but to realize a concurrent model of the real inertial section of the controlled member. The disparity between the current value of the water-level in the shell and the output from the inertial section of the controlled-member model is fed to the input of the external-disturbance equivalent compensating device. This allows employing the compensating device in closed circuit, and consequently, the regulation quality improves under the influence of any external disturbances. The comparative analysis of the modeling results of the Cascade-System Automatic Regulation (CSAR) with PID-regulator adjusted according to the foreign  methods  and  of  the  proposed  invariant  system  shows  considerable  improvement in regulation quality of the latter, viz. : system performance grows 2,5 times when working through the task jump, the peak value of overcorrection lowers from 42,5 to 10,0 %; while working through the internal disturbance, the regulating time reduces by 33 %, the maximum dynamic error of the regulation lowers by 65 %; the time of external combustion disturbance workout completion reduces two times, the maximum dynamic error of regulating – by 63 %; the maximum dynamic error of regulation while working through external disturbance with overheated steam rate diminishes by 71 %, the regulating time reduces by 1,5 times.